2006
DOI: 10.1186/1742-9994-3-12
|View full text |Cite
|
Sign up to set email alerts
|

Control of annual reproductive cycle in the subtropical house sparrow (Passer domesticus): evidence for conservation of photoperiodic control mechanisms in birds

Abstract: BackgroundIn many birds, day length (=photoperiod) regulates reproductive cycle. The photoperiodic environment varies between different seasons and latitudes. As a consequence, species at different latitudes may have evolved separate photoperiodic strategies or modified them as per their adaptive need. We studied this using house sparrow as a model since it is found worldwide and is widely investigated. In particular, we examined whether photoperiodism in house sparrows (Passer domesticus) at 27°N, 81°E shared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 54 publications
3
12
0
Order By: Relevance
“…The gonads regressed in summer month (June) when the day lengths were still longer than the spring months indicating the onset of photorefractoriness. This post reproductive refractory period in the tree sparrow is very much similar to what has been described in the annual reproductive cycles of many bird species [39-42]. The annual reproductive cycle of tree sparrow can be divided into four distinct phases with single annual reproductive peak, i.e., preparatory (December-January), progressive (February-March), reproductive (April-May) and regressive (June-November) phases.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…The gonads regressed in summer month (June) when the day lengths were still longer than the spring months indicating the onset of photorefractoriness. This post reproductive refractory period in the tree sparrow is very much similar to what has been described in the annual reproductive cycles of many bird species [39-42]. The annual reproductive cycle of tree sparrow can be divided into four distinct phases with single annual reproductive peak, i.e., preparatory (December-January), progressive (February-March), reproductive (April-May) and regressive (June-November) phases.…”
Section: Discussionsupporting
confidence: 68%
“…Thus, the active period of gonadal function was longer in tree sparrows than in the house sparrows in the subtropics. Molt began in the same month (June) and completed two months earlier in September in house sparrow [39]. Another study on house sparrows at 52°N reported peak testicular development in May, similar to tree sparrow but full testicular regression was observed one month earlier in August [40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The same hypotheses are generally applicable to the study of intraspecific variation in avian life-cycles (e.g. Trevedi et al 2006). Fig.…”
Section: Conclusion and Future Challengesmentioning
confidence: 93%
“…Gwinner and Scheuerlein (1999) have suggested that the high plasticity of African stonechats towards photoperiodic conditions outside their present distributional range may be a consequence of this tropical population having been founded by (or having interbred with) individuals from northern, migratory populations. Phenotypic plasticity retained in a phylogenetic lineage may be selectively neutral under current environmental circumstances, but could come into play when birds change their distributions Trevedi et al 2006). Alternatively, selection may still maintain a photoperiodic response in tropical populations because birds may use minimal seasonal changes in day-length or Conover and Schultz 1995).…”
Section: S462mentioning
confidence: 99%